CEO Duality is related to the Firm Performance: The impact of CEO duality and corporate governance on the performance of IT companies in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Does CEO duality – the act of one individual serving both as an association's CEOand board seat – add to or hinder firm execution? Organization hypothesis proposes that CEO duality is awful for execution since it bargains the checking and control of the CEO. we break down the connection between Chief duality and execution (ROA or ROE). Experimental discoveries show that CEO duality is emphatically/contrarily related with execution. This paper contributes to the existing literature on corporate governance and firm performance by introducing a framework in identifying and analyzing variables that affect the relationship between CEO duality and firm performance. As India is the biggest hubs for the Information technology (IT) companies and they have impacted the industry in a big way due to several reasons in which their effective governance is also an important means that shape positively the performance of the companies. So, the study mainly focused to ascertain the effect of corporate governance aspects on the performance of selected IT companies in India along with their year wise performance.